Region-specific irradiation system with heavy-ion microbeam for active individuals of Caenorhabditis elegans. (7th September 2017) - Suzuki, Michiyo; Hattori, Yuya; Sakashita, Tetsuya; Yokota, Yuichiro; Kobayashi, Yasuhiko; Funayama, Tomoo
Abstract: Radiation may affect essential functions and behaviors such as locomotion, feeding, learning and memory. Although whole-body irradiation has been shown to reduce motility in the nematode Caenorhabditis elegans, the detailed mechanism responsible for this effect remains unknown. Targeted irradiation of the nerve ring responsible for sensory integration and information processing would allow us to determine whether the reduction of motility following whole-body irradiation reflects effects on the central nervous system or on the muscle cells themselves. We therefore addressed this issue using a collimating microbeam system. However, radiation targeting requires the animal to be immobilized, and previous studies have anesthetized animals to prevent their movement, thus making it impossible to assess their locomotion immediately after irradiation. We developed a method in which the animal was enclosed in a straight, microfluidic channel in a polydimethylsiloxane chip to inhibit free motion during irradiation, thus allowing locomotion to be observed immediately after irradiation. The head region (including the central nervous system), mid region around the intestine and uterus, and tail region were targeted independently. Each region was irradiated with 12 000 carbon ions ( 12 C; 18.3 MeV/u; linear energy transfer = 106.4 keV/μm), corresponding to 500 Gy at a φ20 μm region. Motility was significantly decreased by whole-body irradiation, but not by irradiation of any of the individual regions, including the central nervous system. This suggests that radiation inhibits locomotion by a whole-body mechanism, potentially involving motoneurons and/or body-wall muscle cells, rather than affecting motor control via the central nervous system and the stimulation response.